Toolkit to advance gender equality in agrifood value chains - Shijagurumayum, Meghajit; Elias, Marlène; Morgan, Miranda (CGIAR System Organization, 2024)
Assessing and advancing gender equality in agrifood value chains: A toolkit for firms and voluntary sustainability systems.